Insights into the Thriving of Bacillus megaterium and Rhodotorula mucilaginosa in Mining Areas: Their Adaptation and Tolerance Under Extreme Levels of Cu and Mn - Alfonso Álvarez-Villa; Maribel Plascencia-Jatomea; Kadiya Calderón; Katiushka Arévalo-Niño; Guadalupe López-Avilés; Francisco Javier Almendariz-Tapia (Microbiology Research, 2025)
Understanding microbial adaptation and tolerance based on the cellular concentration and biosorption capacity provides critical insights for evaluating microbial performance under heavy metal stress, which is essential for selecting efficient strains or consortia for bioremediation applications. In this study, the adaptation and tolerance of Bacillus megaterium and Rhodotorula mucilaginosa to elevated concentrations of copper (Cu) and manganese (Mn) were investigated by introducing the maximum adaptation concentration (MAC) alongside the maximum tolerable concentration (MTC) and the minimum inhibitory concentration (MIC). A Gaussian model was fitted to the relative growth responses to estimate the MACs, MTCs, and MICs. B. megaterium exhibited MACs of 4.6 ppm Cu and 393.9 ppm Mn, while R. mucilaginosa showed MACs of 59.6 ppm Cu and 64.4 ppm Mn, corresponding to concentrations that stimulated their maximum cell density. A biosorption analysis revealed average capacities of 6.3 ± 5.3 mg Cu/g biomass and 28.6 ± 17.2 mg Mn/g biomass, positively correlated with the MTCs, indicating enhanced metal uptake under sublethal stress. The co-culture assays demonstrated dynamic microbial interactions shaped by the type and concentration of metal, including coexistence, competitive substitution, and dominance by tolerance. These findings support the use of MACs as indicators of growth stimulation and MTCs as thresholds for enhanced metal uptake, providing a dual-parameter framework for selecting metallotolerant microorganisms for metal recovery strategies.